The Effect of Motivation, Work Environment And Human Resources Development on Employee Performance Through Servant Leadership as A Mediation at PT. Indospring Tbk - Dedy Kurniawan; Eva Desembrianita; Djoko Soelistya (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
Business competition in every company requires companies or organizations to create high-quality employee performance in order to develop the organization.Work motivation is very important because with work motivation, employees will be more enthusiastic in carrying out the tasks given and can improve employee performance. To further clarify the cause of the decline in employee performance, researchers see that there is work motivation that affects the decline in employee performance at PT Indospring Tbk. Indications of decreased motivation can be seen from the fairly high level of employee absenteeism. This study is about the effect of Motivation (X1), Work Environment (X2), and HR Development (X3) on Employee Performance (Y) through Servant Leadership (Z) as a mediating variable at PT Indospring Tbk. This quantitative method is applied to evaluate large populations or samples. the results of the data analysis that have been described are .Motivation has a positive and significant effect on Employee Performance, the Work Environment does not have a significant effect on Employee Performance,HR Development does not have a significant effect on Employee Performance,Motivation has a positive and significant effect on Servant Leadership,Work Environment has a positive and significant influence on Servant Leadership,Human Resource Development has a positive and significant influence on Servant Leadership,Servant Leadership has a positive and significant influence on Employee Performance,Motivation has a positive and significant influence on Employee Performance through Servant Leadership,Work Environment has a positive and significant influence on Employee Performance through Servant Leadership,Human Resource Development has a positive and significant influence on Employee Performance through Servant Leadership.